Evaluation, Language, and Untranslatables. (March 2017) - Dahler-Larsen, Peter; Abma, Tineke; Bustelo, María; Irimia, Roxana; Kosunen, Sonja; Kravchuk, Iryna; Minina, Elena; Segerholm, Christina; Shiroma, Eneida; Stame, Nicoletta; Tshali, Charlie Kabanga
The issue of translatability is pressing in international evaluation, in global transfer of evaluative instruments, in comparative performance management, and in culturally responsive evaluation. Terms that are never fully understood, digested, or accepted may continue to influence issues, problems, and social interactions in and around and after evaluations. Their meanings can be imposed or reinvented. Untranslatable terms are not just "lost in translation" but may produce overflows that do not go away. The purpose of this article is to increase attention to the issue of translatability in evaluation by means of specific exemplars. We provide a short dictionary of such exemplars delivered by evaluators, consultants, and teachers who work across a variety of contexts. We conclude with a few recommendations: highlight frictions in translatability by deliberately circulating and discussing words of relevance that appear to be "foreign"; increase the language skills of evaluators; and make research on frictions in translation an articulate part of the agenda for research on evaluation.